Full field modal measurement with a single standard camera. (August 2018) - Jailin, Clément
Highlights: 8 full field vibration modes can be identified with a single standard camera. The procedure is based on deflectometry, DIC and principal component analysis. kHz frequency modes are measured with slow acquisition speed. 6 out of 8 experimental modes correspond with finite element simulations. Abstract: The full field measurement of 8 vibration modes of a cantilever plate, up to the kHz frequency is performed using a single standard camera. The image acquisition is carried out at low rate but using fast exposure time (1/4000 s) that "freezes" a part of the motion. A deflectometry setup coupled with digital image correlation analysis allows angle fields, then deflection fields, to be measured. An out–of–plane displacement database is generated from all stored fields. This snapshot library is finally post-processed using principal component analysis techniques and adapted weights that enable space vibration fields to be extracted. A test case is performed on a reflecting cantilever steel plate. 370 deflection fields are measured allowing 8 space vibration fields to be extracted. The natural frequencies of those modes are estimated using the Rayleigh ratio. A coarse and visual comparison with a numerical simulation shows similar results for 6 of the 8 space modes.